Effect of characteristics of (Sm,Ce)O2 powder on the fabrication and performance of anode-supported solid oxide fuel cells - Ai, Na; Chen, Kongfa; Liu, Shaomin; Lu, Z.; Su, W.; Jiang, San Ping (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Effect of characteristics of Sm0.2Ce0.8O1.9 (SDC) powder as a function of calcination temperature on the fabrication of dense and flat anode-supported SDC thin electrolyte cells has been studied. The results show that the calcination temperature has a significant effect on the particle size, degree of agglomeration, and sintering profiles of the SDC powder. The characteristics of SDC powders have a significant effect on the structure integrity and flatness of the SDC electrolyte film/anode substrate bilayer cells. The SDC electrolyte layer delaminates from the anode substrate for the SDC powder calcined at 600 °C and the bilayer cell concaves towards the SDC electrolyte layer for the SDC powder calcined at 800 °C. When the calcinations temperature increased to 1000 °C, strongly bonded SDC electrolyte film/anode substrate bilayer structures were achieved. An open-circuit voltage (OCV) of 0.82–0.84 V and maximum power density of ~1 W cm−2 were obtained at 600 °C using hydrogen as fuel and stationary air as the oxidant. The results indicate that the matching of the onset sintering temperature and maximum sintering rate temperature is most critical for the development of a dense and flat Ni/SDC supported SDC thin electrolyte cells for intermediate temperature solid oxide fuel cells.